Process management and technological challenges in the aspect of pernament magnets recycling - the second life of neodymium magnets - Kapustka, Katarzyna; Ziegmann, Gerhard; Klimecka-Tatar, Dorota; Nakonczy, Sara (Manufacturing Technology Journal, 2020)
Very dynamic development in the field of computerization and industry robotization, as well as an im-plementation of the Industry 4.0 assumptions are the main reason for the increased demand for magnetic materials. The limited rare earths availability and the sustainable development in the field of material engineering indicate that the methods of recycling magnetic materials from Waste of Electrical and Electronic Equipment are necessary. This paper presents the impovement stages of magnets recovery process - extrusion process of magnetic scraps/particles with polymer (magnetic scraps and particles obtained from WEEE). The process is developed based on the Process Failure Mode and Effects Analy-sis. The reserch pointed the irregularities, that pose the greatest risk of failure in the process. The paper presents changes in the process based on the values of the indicators: severity (S), probability of occur-rence (O), probability of detection (D) and the Risk Performance Number (RPN). Based on the PFMEA, 5 operations were added to the process. Due to changes in the process course, it is possible to minimize the effects of the irregularities occurrence.
Keywords: NdFeB; neodymium magnets; recycling; magnets recycling; magnets recovery; FMEA